SITUATIONAL ANALYSIS AND PROGRAMMATIC NEEDS ASSESSMENT FOR HIV/AIDS CONTROL TO ACHIEVE THE 95-95-95 STRATEGY - Muhammad Azwar; Zainuddin Zainuddin; Yuding Gassing; Munadhir Munadhir; Ibnul Al Jauzi Amri; Yuliyanti Setiawati (Indonesian Journal of Health Science, 2026)
The 95-95-95 strategy aims to control the Human Immunodeficiency Virus (HIV) and Acquired Immune Deficiency Syndrome (AIDS) HIV/AIDS  epidemic by ensuring that 95% of People Living With HIV (PLHIV) know their status, 95% of those diagnosed receive antiretroviral therapy  Antiretroviral Therapy (ART), and 95% of those on treatment achieve viral suppression. Despite national commitments, Indonesia’s progress especially in South Sulawesi remains below target. This study assessed the HIV/AIDS program situation and needs in Makassar City using a rapid assessment with a mixed-methods approach, prioritizing quantitative data. A total of 96 respondents completed structured questionnaires, and 13 individuals participated in focus group discussions. Findings indicate persistent barriers to testing, treatment access, and adherence, including stigma, low health literacy, side effects, and inadequate support systems. While some PLHIV reported consistent treatment and clinical improvement, non-adherence was still observed. Programmatic needs include targeted health education, supportive policies for key populations, improved communication skills among outreach workers, and non-discriminatory health services. Addressing these gaps requires community-based, evidence-driven interventions to optimize the HIV care continuum. Strengthening stakeholder collaboration and tailoring programs to the real needs of key populations are crucial to accelerate progress toward achieving the 95-95-95 targets and ending the HIV epidemic by 2030.